THE IMPORTANCE OF CULTURAL CONTEXT IN LANGUAGE TEACHING (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2025)
Language and culture are deeply interconnected, making cultural context a vital component of effective language teaching. This article explores the significance of cultural context in language learning, highlighting how cultural awareness enhances communication, improves comprehension, and fosters intercultural competence. It also presents practical strategies for integrating cultural elements into language instruction.